2022
DOI: 10.3390/en15093262
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Elitist Approach to the Design of Axial Flux Permanent Magnet Synchronous Wind Generators (AFPMWG)

Abstract: This paper addresses an integrated and developed approach to the design of an Axial Flux Permanent Magnet Wind Generator (AFPMWG). The proposed analytical method of design employs the size equations and precise inductance calculations simultaneously, as well as considering the mechanical constraints of the back-iron disc of the rotor. An Elitist Genetic Algorithm (EGA), such as a high capability optimization method, has been used to solve the equations and design of a wind generator with predefined rating powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Pada bagian piringan stator dipasang kumparan, sedangkan pada bagian piringan rotor dipasang magnet permanen. Untuk mengurangi torsi awal yang besar, maka inti stator dibuat dari bahan non magnetik, seperti bahan diamagnetic atau paramagnetic [8]. Hal ini akan mengurangi tarikan medan magnet terhadap stator.…”
Section: Pendahuluanunclassified
“…Pada bagian piringan stator dipasang kumparan, sedangkan pada bagian piringan rotor dipasang magnet permanen. Untuk mengurangi torsi awal yang besar, maka inti stator dibuat dari bahan non magnetik, seperti bahan diamagnetic atau paramagnetic [8]. Hal ini akan mengurangi tarikan medan magnet terhadap stator.…”
Section: Pendahuluanunclassified
“…The optimization design combination was verified in the 3D-FEA model, and the results showed that the efficiency of AFPM motor was up to 91.5 %. Additionally, some studies used hybrid algorithms with GA to optimize the design of AFPM motors, such as a hybrid genetic algorithm (HGA) combining simulated annealing and father-offspring selection [77], the elitist genetic algorithm (EGA) [87], the non-dominated sorting genetic algorithm (NSGA-II) [88], etc.…”
Section: Optimization Designmentioning
confidence: 99%
“…The optimization design combination was verified in the 3D-FEA model, and the results showed that the efficiency of AFPM motor was up to 91.5%. Additionally, some studies used hybrid algorithms with GA to optimize the design of AFPM motors, such as a hybrid genetic algorithm (HGA) combining simulated annealing and father-offspring selection [77], the elitist genetic algorithm (EGA) [87], the non-dominated sorting genetic algorithm (NSGA-II) [88], etc. With the further development of efficient computer system and optimization theory, new multi-objective optimization algorithms such as particle swarm optimization (PSO) [89,90], bat optimization (BO) [91] and the Taguchi algorithm [92] have also been applied to the optimization design of AFPM motors.…”
Section: Optimization Designmentioning
confidence: 99%
“…Compared with the conventional radial flux permanent magnet (PM) machine, the axial flux permanent magnet (AFPM) machine can be used in some special applications such as electric vehicles [1], wind turbine systems [2], and unmanned aerial vehicles [3] due to its short axial size, compact structure, disk-shaped profile, and high efficiency. The AFPM machine has a variety of classical structures; wherein, the configuration with double rotors and a single stator is preferred chiefly [4,5], and the stator core is not necessarily required to form a closed magnetic circuit in the design.…”
Section: Introductionmentioning
confidence: 99%
“…The AFPM machine has a variety of classical structures; wherein, the configuration with double rotors and a single stator is preferred chiefly [4,5], and the stator core is not necessarily required to form a closed magnetic circuit in the design. By eliminating the iron core of the stator, the coreless AFPM machine has the following advantages [6][7][8]: (1) The quality and cost of the machine are reduced; (2) The loss of the stator core and the cogging torque of the machine are eliminated; (3) The inductance of windings is small, and the influence of the stator current on the air gap flux density is almost negligible; (4) The ability of overload is greatly improved; (5) The arrangement of coils is more flexible and not constrained by slots and teeth of the stator.…”
Section: Introductionmentioning
confidence: 99%